IMPROVING EARLY CHILDHOOD SOCIAL SKILLS THROUGH THE GOBAK SODOR GAME AT TK IT AL FATHANIYAH ACEH TENGGARA - Sari, Nova; Ahmad Syukri Sitorus2, Ahmad c (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study aims to improve early childhood social skills through the Gobak Sodor game. The method used is Classroom Action Research (CAR) with observation and interview techniques. The research was conducted at TK IT Al Fathaniyah, Aceh Tenggara, with 15 children aged 4-5 years as the subjects. The research process took place from May 5 to June 6, 2024. In the pre-cycle stage, only 13.3% of the children showed good social skills. Subsequently, two action cycles were carried out. In cycle I, although social skills improved to 46.7%, the success target was not yet achieved. Improvements were made in cycle II by adding small rewards as motivation, resulting in 80% of the children achieving significant social development. The research results show that the Gobak Sodor game is effective in enhancing early childhood social skills. The consistent improvement from the pre-cycle to cycle II proves that this traditional game can be an attractive and effective learning medium. This game not only helps children interact and cooperate but also increases their motivation and enthusiasm in the learning process. Therefore, the use of the Gobak Sodor game as a learning tool can be recommended to support the social development of early childhood in formal education settings.